Inhibitory Effects of iPSC-MSCs and Their Extracellular Vesicles on the Onset of Sialadenitis in a Mouse Model of Sjögren’s Syndrome - Bo Hai; Taeko Shigemoto-Kuroda; Qingguo Zhao; Ryang Hwa Lee; Fei Liu (Stem Cells International)
No effective treatment for Sjögren’s syndrome (SS), a chronic autoimmune disease affecting mainly salivary and lacrimal glands, is available now. Systemic infusion of allogeneic mesenchymal stem cells (MSCs) isolated from tissues such as bone marrow (BM) alleviated SS in mouse models and a small clinical trial, but further research and application of this MSC therapy were hindered by limited expandability, significant donor variations, and safety concerns of tissue-derived MSCs. To circumvent these issues, we derived MSCs from human iPSCs using an optimized protocol that can be easily scaled up to produce a huge amount of standardized MSCs. Our iPSC-MSCs inhibited the onset of lymphocyte infiltration into salivary glands in the NOD mouse model of SS in the same way as BM-MSCs. Extracellular vesicles (EVs) carry bioactive molecules in the same way as their originating cells and are more stable and considered much safer than cells for therapies. We found that EVs derived from BM-MSCs and iPSC-MSCs suppressed activation of immune cells and expression of proinflammation factors essential for SS progression in vitro and that infusion of iPSC-MSC EVs at the predisease stage decreased the lymphocyte infiltration in salivary glands and serum autoantibody levels in the same way as infusion of BM-MSCs and iPSC-MSCs. These data suggested that iPSC-MSC EVs have the potential to prevent the progression of SS before the onset of sialadenitis.